Pengaruh Jumlah Tumbukan Pada Campuran AC-WC Terhadap Nilai Marshall - Ridho Hafidz; Fatmawati Fatmawati; Sara Wibawaning Respati (Civil Engineering Dept, Balikpapan State Polytechnics, 2024)
Asphalt Concrete Wearing Course (AC-WC) is the surface layer of flexible pavement that directly bears traffic loads and provides driving comfort. This study aims to analyze the effect of varying the number of compaction blows on the Marshall characteristics of AC-WC mixtures and to determine the optimal number of blows according to applicable specifications. The testing methodology adhered to SNI 06-2489-1991 and the Bina Marga Specification 2018 Revision 2, which included comprehensive material testing and Marshall testing for Stability, Flow, Voids in the Mix (VIM), Voids in Mineral Aggregate (VMA), and Voids Filled with Bitumen (VFB). The results indicate that increasing the number of blows from 2x50 to 2x85 significantly impacts the mixture's properties. Stability, VFB, and Marshall Quotient values increased with more blows, while Flow, VIM, and VMA decreased. Average Stability rose from 802.2 kg (2x50 blows) to 2657.1 kg (2x85 blows). Conversely, average Flow decreased from 6.5 mm to 2.5 mm, VIM from 9.0% to 1.3%, and VMA from 19.3% to 12.5%. Based on the analysis of all Marshall criteria, the 2x80 blows treatment was identified as the most optimal. At this level, the mixture achieved an ideal balance between strength (Stability of 2214.3 kg) and flexibility (Flow of 3.0 mm) while meeting all specification requirements. This study concludes that compaction effort is crucial for performance and recommends 2x80 blows to produce a superior AC-WC mixture for preventive maintenance purposes.